Financial Feasibility Analysis of Copper Cathode Factory at PT. X in Central Kalimantan - Bahri, Saeful; Oetomo, Dedy Setyo; Hermawan, Asep (Sainteks: Jurnal Sain dan Teknik, 2024)
Indonesia has a lot of promising mineral wealth, one of which is copper, but its processing into cathodes is still minimal while domestic demand is not yet sufficient. In accordance with the strategic downstream investment plan for mineral commodities, especially copper, which has been included in the state downstream document, it requires a comprehensive financial feasibility document, especially for PT. X. The analysis in this research uses a reference capacity of 25,000 tons of cathode. This research aims to determine the technical factors in building a copper cathode factory, determine the amount of investment required in the form of CAPEX and OPEX, and determine its financial feasibility. The method used in financial feasibility analysis at PT. This X is Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). Based on the research results, it was found that the total CAPEX (Capital Expenditure) costs that had to be incurred were $ 330,589,628 and the total OPEX (Operational Expenditure) costs that had to be spent was $ 312,257,456 with an NPV value of $ 27,505,439, an IRR value of $ 27,505,439. 15.1%, and PP value for 6 years 10 months. Therefore, the project to build a copper cathode factory at PT. X is worth continuing.